Potential Therapeutic Effects of Sodium Glucose-linked Cotransporter 2 Inhibitors in Stroke - Fatima Alzahra Al Hamed (17115562) (2020)
Purpose Stroke is the second leading cause of death and the third leading cause of disability worldwide. Diabetes mellitus and the associated hyperglycemia are important risk factors for acute ischemic stroke and are associated with poor prognosis. Neurovascular protection is an important therapeutic target to achieve in patients with stroke, especially in those receiving thrombolytic reperfusion therapy. Sodium glucose-linked cotransporter 2 (SGLT2) inhibitors are a novel class of antidiabetic agents that target SGLT2. Hyperglycemia exacerbates the neuronal damage through the SGLT2 transporter. The purpose of this narrative review is to discuss the pleiotropic effects of SGLT2 inhibitors and their role in the treatment and prevention of ischemic stroke in experimental and clinical studies. Methods We searched the PubMed database using different term combinations from the date of inception to May 2019. Deselection methods were followed to exclude unrelated articles. The total number of articles included was 14. Findings In experimental models, SGLT2 inhibitors have a protective mechanism against neuronal dysfunction and damage through various mechanisms. From a clinical perspective and based on current evidence, SGLT2 inhibitors reduce the risk of cardiovascular events, especially in patients with heart failure. Implications SGLT inhibitors may have neurologic and/or vascular protective effect after acute ischemic stroke based on experimental studies. However, getting an accurate judgment of this effect is hard to achieve because only a few animal studies are available. Furthermore, and unlike animale studies, clinical studies provided uncertain answers on whether SGLT2 inhibitors would provide neuroprotective effect. In addition, several studies used combination of drugs along with SGLT2 inhibitors. Conclusions It is unlikely that SGLT inhibitors have a positive or negative effect on stroke risk, but the question that remains unanswered is whether SGLT inhibitors can yield a protective effect after acute ischemic stroke. Future observational studies and registries may be the first step to help answer this question. Other Information Published in: Clinical Therapeutics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clinthera.2020.09.008